AN ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACTS OF ELEANOR FALCO IN ‘TO CATCH A KILLER’ MOVIE BY DAMIÁN SZIFRÓN - Monangin, Christa; Andries, Fivy A.; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to find out the types of directive illocutionary acts and explain how perfomerd Eleanor Falco in "To Catch a Killer"movie. This research involves qualitative methods. The steps taken by researchers to collect data were watching movie, then marking the types of directives than identified as asking, requesting, commanding, forbidding, and suggesting. Data were categorized based on the Vanderveken classifications (1990). Three steps proposed by Miles and Huberman for data analysis were used in this research: data reduction, data display, and data verification/conclusion. The findings of this research reveal a total of 33 Speech acts uttered by Eleanor Falco in the movie “To Catch a Killer” there are 16 asking, 10 requesting,4 Commanding,1 Forbidding, and 2 Suggesting. It is recommended research be a reference for readers and other researchers in studying and interpreting directive illocutionary act sentences in movies or other literary works.